Formulation and in vitro evaluation of flurbiprofen-polyethylene glycol 20000 solid dispersions - Bhaskar Daravath and Rama Rao Tadikonda (Journal of Applied Pharmaceutical Science, 2014)
Solid dispersion is one of the most widely used methods to enhance the solubility and dissolution rate of poor water soluble drugs. In the present study, flurbiprofen solid dispersions were prepared using solvent evaporation method by incorporating polyethylene glycol 20000 and evaluated for solubility studies, drug-carrier compatibility studies and in vitro dissolution studies. From the solubility studies, formulations F4 were selected to prepare in the form of tablets and compared with control tablets (conventional tablets using pure drug). From the results of in vitro dissolution study, tablets containing polyethylene glycol 20000 showed almost complete drug release within the 15 min. The percent drug release in 15 min (Q15) and initial dissolution rate for formulation F4 was 99.26±1.12%, 6.62%/min. These were very much higher compared to control tablets (34.95±1.29%, 2.33%/min). The relative dissolution rate was found to be 2.84 and dissolution efficiency was found to be 57.48 and it is increased by 3.5 fold with F4 formulation compared to control tablets (17.91). From the above results, it is concluded that the formulation of solid dispersions using polyethylene glycol 20000 is a suitable approach to improve the solubility and dissolution rate of flurbiprofen.
Keywords: Dissolution efficiency, Initial dissolution rate, Relative dissolution rate, Solvent evaporation method, Solubility studies.